Support in Shaping Pre-Diabetes Preventive Behavior Among Urban Productive-Age: A Path Analysis Study - Sobar Darmadja; Risky Kusuma Hartono (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2025)
The productive-age population in urban areas is susceptible to diabetes, often without awareness of their pre-diabetic condition. This study examines the various roles in pre-diabetes preventive behavior among the productive-age group in urban communities. A quantitative cross-sectional design was employed, involving 363 respondents aged 20-69 years, selected through simple random sampling. The variables investigated include mindset, motivation, health literacy, social support, family support, and exposure to health information, all of which play significant leveraging roles in pre-diabetes preventive behavior. Path-based multivariate regression analysis was used to explore the direct and indirect influences among these variables. Health literacy was found to play a significant role in shaping mindset, which subsequently contributes to pre-diabetes preventive behavior, as demonstrated by family support (β = 0.010; p = 0.013). Social support (β = 0.051; p = 0.006) and motivation (β = 0.059; p = 0.005) also proved to have a meaningful impact. This study concluded that prevention of the high risk of pre-diabetes in the productive-age group, interventions should focus on improving health literacy, strengthening social and family support, and fostering motivation. The findings highlight the critical need for targeted health education and community-based support systems to address the growing risk of diabetes among urban populations, particularly those in the productive age group who may be unaware of their pre-diabetic status.